2017
DOI: 10.3389/fphar.2017.00697
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Alzheimer’s Studies on β-Sitosterol Isolated from Polygonum hydropiper L.

Abstract: The family Polygonaceae is known for its traditional use in the management of various neurological disorders including Alzheimer’s disease (AD). In search of new anti-AD drugs, β-sitosterol isolated from Polygonum hydropiper was subjected to in vitro, in vivo, behavioral and molecular docking studies to confirm its possibility as a potential anti-Alzheimer’s agent. The in vitro AChE, BChE inhibitory potentials of β-sitosterol were investigated following Ellman’s assay. The antioxidant activity was tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
147
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(148 citation statements)
references
References 79 publications
0
147
1
Order By: Relevance
“…are among the major health problems affecting the lives of individuals, particularly the elderly ones globally (Ali et al, ). Ayaz, Junaid et al () reported that Alzheimer’s disease is the most common neurological disorder, characterized with gradual memory loss, cognitive dysfunctions, behavioral turbulence, etc., with more than 33.9 million people suffering from this disorder worldwide with a projection of three folds increase by the next 40 years. In spite of the presence of known medicine used in the treatment of these diseases, (especially Alzheimer’s disease) their related complications (e.g., erectile dysfunction, hypertension, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…are among the major health problems affecting the lives of individuals, particularly the elderly ones globally (Ali et al, ). Ayaz, Junaid et al () reported that Alzheimer’s disease is the most common neurological disorder, characterized with gradual memory loss, cognitive dysfunctions, behavioral turbulence, etc., with more than 33.9 million people suffering from this disorder worldwide with a projection of three folds increase by the next 40 years. In spite of the presence of known medicine used in the treatment of these diseases, (especially Alzheimer’s disease) their related complications (e.g., erectile dysfunction, hypertension, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Alpha‐tocopherol is a potent antioxidant and compounds with strong antioxidant properties and are able to attenuate neurodegeneration and retard the progression of AD (Kumar & Khanum, ). Furthermore, stigmasterol and beta‐sitosterol have also been reported to exhibit neuroprotective effects (Ayaz et al, ; Haque & Moon, ). The observed total phenol and flavonoid contents of the extracts suggests the presence of some phenolic compounds in the seaweeds.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the compounds identified in the extracts may contribute to their cholinesterase inhibitory activities. Docking studies conducted by Ayaz et al () revealed that beta‐sitosterol effectively binds to the asparagine 285 and glycine 71 residues of AChE and BChE via hydrogen bonds, respectively, hence reducing the activity of the enzyme. Similarly, beta‐amyrone also exhibited moderate anti‐acetylcholinesterase activity (Mollataghi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In old age people (above 60 years), their frequencies are high. [8] Acetylcholine (ACh) and Butyrylcholine (BCh) are important neurotransmitters that are involved in acquisition and storage of memories, and in the transmission of impulses across the synapse. Usually in the neurodegenerative processes the level of neurotransmitters: ACh and BCh exhausted.…”
Section: Introductionmentioning
confidence: 99%